Cascade fragmentation: deviation from power law in primary radiation damage. Issue 5 (3rd September 2017) - Sand, A. E.; Mason, D. R.; De Backer, A.; Yi, X.; Dudarev, S. L.; Nordlund, K.
ABSTRACT: The sizes of defect clusters, produced in materials by energetic ion or neutron impacts, are critically important input for models describing microstructural evolution of irradiated materials. We propose a model for the distribution of sizes of vacancy and self-interstitial defect clusters formed by high-energy impacts in tungsten, and provide new data from in situ ion irradiation experiments to validate the model. The model predicts the statistics of sub-cascade splitting and the resulting distribution of primary defects extending over the entire range of cluster sizes, and is able to provide initial conditions for quantitative multi-scale simulations of microstructural evolution. GRAPHICAL ABSTRACT: IMPACT STATEMENT We present a model, parameterized for tungsten, for the distribution of defect sizes in primary radiation damage, as an essential step in multi-scale modelling of microstructural evolution in irradiated materials.